An investigation into the impact of student questions on formative assessment in flipped sixth form biology lessons - Bonsall, H (2017)
This investigation aimed to determine whether formative assessment (AfL) in flipped Sixth Form Biology lessons can be made more inclusive by encouraging student questions through various teaching strategy innovations. The literature review suggests student questions could play an important role in AfL. However, many studies suggest students ask few questions in lessons, for a number of reasons. The following research questions explored which factors encouraging or inhibiting student questions might be relevant to the selected student cohort, to develop innovations: 1. Which Sixth Form students ask few questions over the course of two or three flipped Biology lessons? 2. What encourages and discourages Sixth Form student questions in lessons in this school? Five Sixth Form Biology teachers, from the same school, participated in the research and, of the students in their classes, 56 completed tally sheets, monitoring the number of questions they asked in flipped lessons, and questionnaires, determining their perception of the quality of AfL taking place. 11 students participated in focus group interviews before the innovations, to help develop them, and after the innovations, to evaluate their success. The following research questions were used to evaluate the innovations' success: 3. To what extent can changes in teaching strategy, based on the focus group interview data, affect the median number and statistical range of student questions asked in flipped Biology lessons? 4. To what extent can changes in teaching strategy, based on the focus group interview data, affect student perceptions of AfL in flipped Biology lessons? 5. To what extent does the number of questions asked by students correlate with their perception of AfL in flipped Biology lessons? There is some evidence of partial success of some teaching strategies implemented in encouraging student questions. Evidence suggesting the innovations resulted in more inclusive AfL was weak. An unexpected, weak negative correlation between the number of questions asked by students in flipped lessons and their perceptions of the quality of AfL taking place within these lessons was revealed.